Ikhsaka Banu's reconciliation and resistance to the traumatic discourse of postcolonial subjects - Sanjaya, Angga Trio; Wei , Zhang (BAHASTRA, 2023)
The discourse of colonial and colonized conflicts is oriented in the form of resentment and hatred of the colonized community as part of the causality of traumatic events. The wounds of the past are then passed down through the concept of memory transmission both by famillial mechanism memory and affillial memory by first-generation to post-generation. It is this hereditary traumatic condition that contributes to maintaining the discourse of inferiority and binaryism between East and West. Thus, the purpose of this study is to describe the conflicts of colonizers and postcolonial colonizers as well as examine the efforts of Iksaka Banu to release these traumatic shackles through reconciliation and resistance efforts. This research method uses Teun van Critical Discourse Analysis (AWK). Dijk which is based on the analysis of the text dimension, the social cognition dimension, and the social context dimension. Data collection techniques in this study apply listening methods and advanced recording techniques, and document review techniques. The results showed that (1) A review of the dimensions of the text showed a reconstruction of the ambivalence and traumatic of Western subjects in the short stories of Iksaka Banu; (2) A study of the dimensions of social cognition shows that the reconstruction pattern of ambivalence and traumatic of the Western subject is used as Iksaka Banu's strategy to carry out traumatic reconciliation of colonized subjects as well as resistance to Western domination and hegemony; (3) A study of the social context shows two findings of the problem, First, the existence of social inequality over the mechanisms of Western domination and hegemony; Second, even so, Indonesian society is still confined by the problem of trauma while awareness of the subject's position on the condition of social reality cannot be managed as a potential resistance